2018
DOI: 10.1016/j.ajpath.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and Extraterminal (BET) Proteins Regulate Hepatocyte Proliferation in Hepatocyte-Driven Liver Regeneration

Abstract: Bromodomain and extraterminal (BET) proteins recruit key components of basic transcriptional machinery to promote gene expression. Aberrant expression and mutations in BET genes have been identified in many malignancies. Small molecule inhibitors of BET proteins such as JQ1 have shown efficacy in preclinical cancer models, including affecting growth of hepatocellular carcinoma. BET proteins also regulate cell proliferation in nontumor settings. We recently showed that BET proteins regulate cholangiocyte-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…A recent study showed that BET protein inhibition inhibits liver regeneration by inhibiting the Wnt signaling pathway 38. Our data demonstrate that the BET proteins inhibition affect the liver regeneration by inhibiting the YAP/TAZ-Notch1-NICD axis, and uncovered the role of YAP/TAZ-Notch1-NICD in liver regeneration.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study showed that BET protein inhibition inhibits liver regeneration by inhibiting the Wnt signaling pathway 38. Our data demonstrate that the BET proteins inhibition affect the liver regeneration by inhibiting the YAP/TAZ-Notch1-NICD axis, and uncovered the role of YAP/TAZ-Notch1-NICD in liver regeneration.…”
Section: Discussionsupporting
confidence: 57%
“…They mediate different steps of BEC-driven regeneration in zebrafish, BEC dedifferentiation into LPC, proliferation of LPC and redifferentiation into new hepatocytes and their maturation [ 28 ]. In addition, BET proteins also promote hepatocyte-driven liver regeneration in a zebrafish liver injury model of paracetamol (APAP) overdose ( Table 1 ) [ 26 ]. Importantly, the requirement for BET proteins in both types of liver regeneration is conserved in mice.…”
Section: Awakening the Regenerative Capacity In Different Organsmentioning
confidence: 99%
“…In the choline-deficient ethionine-supplemented CDE-diet mouse model of chronic liver injury that induces BEC-driven regeneration, BET proteins are required for activation of LPC [ 28 ]. In mice after partial hepatectomy, BET proteins are required for hepatocyte proliferation [ 26 ]. These data are of high clinical relevance as the same BET inhibitor, JQ1, has been used in a clinical trial for cancer therapy, including liver cancer.…”
Section: Awakening the Regenerative Capacity In Different Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bromodomains of bromodomain and extraterminal (BET) proteins, which regulate transcription by binding to acetylated lysine residues on histone tails, also regulate hepatocellular proliferation in hepatocyte-driven liver regeneration [116] . Russell et al [116] have shown that the drug JQ1, a specific inhibitor of Brd4 (one of BET proteins), impairs hepatocyte proliferation in partial hepatectomy and acetaminophen-induced liver regeneration with significant reduction in E2f2 genes and cyclin-D1.…”
Section: Epigenetic Regulation Of Liver Regenerationmentioning
confidence: 99%